The Interplay of Capital Structure and Investment under Uncertainty: A Qualitative Synthesis of Structural Models and Empirical Evidence - Erwin Santosa; Moh Zalmi Kahardani; Moh Trisamanta (LPPM STIE Kasih Bangsa, 2026)
This qualitative literature review explores the dynamic relationship between capital structure and investment decisions under uncertainty. Drawing on structural models such as real options and dynamic trade-off theories, as well as empirical studies across diverse economic contexts, the paper synthesizes how firms adapt financing and investment strategies in response to market volatility, policy shifts, and financial constraints. The findings reveal that uncertainty often prompts delayed investment and a preference for financial flexibility, though firm responses vary based on growth potential, credit access, and institutional environments. By integrating theoretical frameworks with empirical evidence, this review highlights key mechanisms and limitations in current scholarship, offering a foundation for future interdisciplinary research